The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jmv.24542
|View full text |Cite
|
Sign up to set email alerts
|

Multiple human papillomavirus infections and type-competition in women from a clinic attendee population in China

Abstract: To investigate the multi-infection patterns and type competition for human papillomavirus (HPV) in Chinese clinic attending women and evaluate the association between the infection status and cancer risk. Three hundred and thirty-two HPV-DNA-positive samples were genotyped for 21 HPVs and tested for 13 types of HPV neutralizing antibody using pseudoviron-based assay. Odds ratios (ORs) were calculated to evaluate the coinfection patterns for both DNA and neutralizing antibody (NAb), and the associations of HSIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Some studies demonstrated that multiple infections displayed a longer duration of HPV infection compared to a single infection, which may result in cervical cancer occurrence ( Kim et al, 2021 ). On the contrary, some studies found that single HPV infection had a higher risk of developing into cervical cancer than multiple infections, the possible pathogenic mechanism of which could be competition or a counterbalance between various HPV subtypes ( Nie et al, 2016 ; Li et al, 2019 ). In our study, the prevalence of single HPV infections was higher than that of double and multiple HPV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that multiple infections displayed a longer duration of HPV infection compared to a single infection, which may result in cervical cancer occurrence ( Kim et al, 2021 ). On the contrary, some studies found that single HPV infection had a higher risk of developing into cervical cancer than multiple infections, the possible pathogenic mechanism of which could be competition or a counterbalance between various HPV subtypes ( Nie et al, 2016 ; Li et al, 2019 ). In our study, the prevalence of single HPV infections was higher than that of double and multiple HPV infections.…”
Section: Discussionmentioning
confidence: 99%
“… 23 However, negative interactions were observed between HPV16 and 52, HPV18 and HPV51/52/58, HPV31 and HPV39/51/52/53/54/58, HPV33 and HPV52/58, HPV58 and HPV52, HPV6 and HPV 39/51/52/53/54/56/58, suggesting the possibility of type replacement between these paired types. Negative associations were also observed for HPV16-52 24 and HPV16-51 25 in Chinese and Danish study respectively. While in other studies, multiple positive associations were observed with no statistically significant negative associations.…”
Section: Discussionmentioning
confidence: 76%